CD44+ and CD31+ extracellular vesicles (EVs) are significantly reduced in polytraumatized patients with hemorrhagic shock – evaluation of their diagnostic and prognostic potential - Weber, Birte; Sturm, Ramona; Henrich, Dirk; Marzi, Ingo; Leppik, Liudmila (Frontiers in Immunology, 2023)
Background: Hemorrhagic shock (HS) is responsible for approximately 2 million deaths per year worldwide and is caused in 80% by polytrauma. These patients need a precise and quick diagnostic, which should be based on a combination of laboratory markers and radiological data. Extracellular vesicles (EVs) were described as potential new markers and mediators in trauma. The aim of the present study was to analyze, whether the surface epitopes of plasma-EVs reflect HS in polytraumatized patients and whether cell-specific EV subpopulations are useful diagnostic tools.Material and Methods: Plasma samples from polytraumatized patients (ISS ≥16) with HS (n=10) and without (n=15), were collected at emergency room (ER) and 24h after trauma. Plasma-EVs were isolated via size exclusion chromatography and EV-concentrations were detected by Coomassie Plus (Bradford) Assay. The EVs subpopulations were investigated by a bead-based multiplex flow cytometry measurement of surface epitopes and were compared with healthy controls (n=10). To investigate the diagnostic and prognostic potential of EVs subpopulations, results were correlated with clinical outcome parameters documented in the electronical patients' record.Results: We observed a significant reduction of the total amount of plasma EVs in polytrauma patients with HS, as compared to polytrauma patients without HS and healthy controls. We found significant reduction of CD42a+ and CD41b+ (platelet-derived) EVs in all polytrauma patients, as well as a reduction of CD29+ EVs compared to healthy volunteers (*p<0.05). CD44+ and CD31+ EVs were specifically altered in patients with HS (*p<0.05). Both EV populations showed a moderate correlation (r² = 0.42) with the transfusion of erythrocyte concentrate, were associated with non-survival and the need for catecholamines (*p<0.05). Conclusion: Our data reveal that polytrauma patients with a hemorrhagic shock are characterized by a reduction of CD44+ and CD31+ plasma-EVs. Both EV populations showed a moderate correlation with the need of erythrocyte transfusion, were associated with non-survival and the need for catecholamines.